Current‐Enhanced Broadband THz Emission from Spintronic Devices. Issue 4 (14th December 2018) - Chen, Mengji; Wu, Yang; Liu, Yang; Lee, Kyusup; Qiu, Xuepeng; He, Pan; Yu, Jiawei; Yang, Hyunsoo
Abstract: An ultra‐broadband terahertz (THz) emitter covering a wide range of frequencies from 0.1 to 10 THz is highly desired for spectroscopy applications. So far, spintronic THz emitters have been proven as one class of efficient THz sources with a broadband spectrum while the performance in the lower THz frequency range (0.1–0.5 THz) limits its applications. In this work, a novel concept of a current‐enhanced broad spectrum from spintronic THz emitters combined with semiconductor materials is demonstrated. A 2–3 order enhancement of the THz signals in a lower THz frequency range (0.1–0.5 THz) is observed, in addition to a comparable performance at higher frequencies from this hybrid emitter. With a bias current, there is a photoconduction contribution from semiconductor materials, which can be constructively interfered with the THz signals generated from the magnetic heterostructures driven by the inverse spin Hall effect (ISHE). These findings push forward the utilization of metallic heterostructure‐based THz emitters on the ultra‐broadband THz emission spectroscopy. Abstract : A novel ultra‐broadband spintronic terahertz (THz) emitter enhanced by a current modulation through the semiconductor channel is demonstrated for the first time. A significant enhancement of the THz signal (up to 2–3 orders) in the frequency range from 0.1 to 0.5 THz without compromising the performance at higher frequencies is achieved, as compared with the typical spin‐based emitters.